Exploiting the Metabolism of the Gut Microbiome as a Vehicle for Targeted Drug Delivery to the Colon - Hamid A. Bakshi; Gerry A. Quinn; Alaa A. A. Aljabali; Faruck L. Hakkim; Rabia Farzand; Mohamed M. Nasef; Naji Abuglela; Prawej Ansari; Vijay Mishra; Ángel Serrano-Aroca; Murtaza M. Tambuwala (MDPI AG, 2021)
The prevalence of colon-associated diseases has increased significantly over the past several decades, as evidenced by accumulated literature on conditions such as Crohn's disease, irritable bowel syndrome, colorectal cancer, and ulcerative colitis. Developing therapeutics for these diseases is challenging due to physiological barriers of the colon, systemic side effects, and the intestinal environment. Therefore, in a search for novel methods to overcome some of these problems, researchers discovered that microbial metabolism by gut microbiotia offers a potential method for targeted drug delivery This overview highlights several drug delivery systems used to modulate the microbiota and improve colon-targeted drug delivery. This technology will be important in developing a new generation of therapies which harness the metabolism of the human gut microflora.